RADIOIODINE THERAPY AS AN EFFECTIVE CONVENIENT MODALITY OF TREATMENT FOR THYROTOXICOSIS: AN ATTEMPT TO SETTLE THE DUST ONCE AND FOR ALL! - CP, Ooi; M, Siruhan; S, Norlela; S, Maimanah; K, Nor Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Thyrotoxicosis when treated inadequately with oral antithyroid drugs for longer than a decade may result in premature cardiovascular morbidity and mortality. In this respect, radioactive iodine therapy (RAI) has been used for more than seven decades in order to achieve lifelong remission. However not all patients become euthyroid or hypothyroid following a single dose of RAI. In view of a recent publication showing a dismal result of RAI therapy (a meager 50% success rate) in a local tertiary institution, we have embarked on a similar quest in order to address this issue once and for all. METHODOLOGY Participants were identified from the list of patients who underwent RAI therapy for thyrotoxicosis in our institution from January 2013 to April 2018. All of the patients were referred for RAI following failure of conventional antithyroid therapy to induce lifelong remission. Patients’ characteristics, clinical outcomes and laboratory results were retrieved from the medical and laboratory records. Descriptive statistics were used to describe the data. Relationships were explored with appropriate statistics with significant findings established at p<0.05. RESULT A total of 168 patients were identified. The mean age was 44.81+15.7 years; 73% (n=123) were females. 73% (n=119) had Graves’ disease and 23% had multinodular goitre (n=39). Majority (88%) had a single course of RAI, whereas 12% needed a second course. The dose used was 15 mCi in 46% and 12 mCi in 48% of cases. Five (3%) patients were lost to follow-up following first RAI. Overall 85% (n=142) of patients achieved remission as defined by hypothyroid or euthyroid state without any further intervention beyond 6 months of RAI. CONCLUSION Our study conclusively support the results obtained from other reputable centres in the West where RAI is effective in rendering hypo- or euthyroid state in more than 85% of patients with thyrotoxicosis following failed conventional antithyroid therapy.